A research on related properties of hybrid benzenoid system. (4th July 2022) - Jiang, Yongsheng; Xie, Dongyang; Xu, Jiabo; Chen, Xing
Abstract: In this paper, we study the planar graph of a class of benzenoid hydrocarbons[7] which contains only regular hexagons and one pentagon. Here we suppose that the pentagon is only on the left side of the polyhexes, for instance, fluorence, coimarone etc[11]. We call them hybrid system. Firstly, by using of BEC code[12] of the polyhexes, we give a algorithm and create a new BEC code which satisfies the condition of the hybrid system and by which we enumerate all the cases. Secondly, we use the adjacency matrix of polyhexes to get the corresponding adjacency matrix of hybrid system.